Characterization of anodizing process on aluminum Al3003 and Al6063 using the multifactorial analysis and robust design techniques. - Vergara Guillén, Leonardo Eladio; Nerey Carvajal, Luis Manuel; Guédez Torcates, Víctor Manuel (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This study pretends to quantify the effect of the process parameters in the anodizing of aluminum Al3003 and Al6063. For it, were made studies of the micro-hardness, roughness, thickness of layer and porosity of the anodized surface, using multifactorial analysis and robust design techniques. The following parameters levels were established: temperature [15°C, 25°C], time [30min; 60min], electrolyte con- centration [1.2M; 2M], current density [1Amp/dm2; 3Amp/dm2], aluminum [Al3003, Al6063], and the plastic deformation [ 0%, 10%, 20%, 30% ], as noise parameter. A combined fractional design 27-2 was proposed, a total of 48 tests were made using sulfuric acid electrolytic solutions. The measurement of micro-hardness was made with an indentador Vickers loaded with 400g; the measurement of roughness Ra was made with a surface roughness tester MITUTOYO SJ-201P; and electronic microscopy was used to observe the porosity and the thickness of the oxide layer. A variance analysis (ANOVA) was made to establish the significant factors and the robustness of the effects in the results. Micro-hardness [HV]: [85.74-308.87]; roughness [Âµm]: [0.45-3.28]; porosity [pores]: [410.72-969.52] and thickness of oxide [Âµm]: [12.82-94.69] results were found. Finally, the best results and their parameters are shown for each response.